The bachelor of Art in Guarani-Spanish bilingualism program and the graduate’s social incorporation (Journal on studies and research of academic knowledge, 2022)
The National University of Itapúa through the Faculty of Humanities, Social Sciences and Guarani Culture with the degree in Guarani-Spanish / Spanish-Guarani Bilingualism from 1999 to the present instructs bilingual professionals in the two official languages of Paraguay, in this context and in order to describe the impact and results of the Bachelor's degree in Guarani-Spanish Bilingualism taking into account the social bond of the graduates, this study was carried out to know whether or not the objectives of the aforementioned degree were achieved. The scope of the research was descriptive because the impact and results of the Bachelor's Degree in Guarani-Spanish Bilingualism were described by determining the functions fulfilled by the graduates, the contributions they provide in the educational field and the evaluation of the relevance of the curriculum. For data collection, a survey was applied through google form due to the pandemic situation the following questions were posed in which different statements with multiple options were asked, as well as some open questions so that the graduates could express their point of view in relation to the career they studied. From the 224 graduates, 162 answered to the survey which represents 72% of graduates. The results obtained were very positive in terms of the training and relevance of the curriculum, most of the graduates are working in a profession related to their training and entered through a competitive examination; teaching is the field where most graduates are working so it is concluded that the graduates are involved according to their training in different areas of education, being preferably in the educational field, they are also in research and in the definition of educational linguistic policies contributing to the achievement of a better quality of life in society
Keywords: Bilingualism; Impact; Training; Pertinence